2019
DOI: 10.1016/j.mineng.2019.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the selective precipitation of iron to produce yellow pigment from acid mine drainage

Abstract: Acid mine drainage (AMD) in the coal mining industry is recognized as one of the major sources of environmental damage. The active treatment of AMD involves adding alkaline reagents to wastewater so as to raise pH and to precipitate dissolved metals in the form of oxides/hydroxides. Studies have shown that yellow pigment (goethite) can be produced from the iron present in AMD. However, the presence of other metals can prevent the formation of pigment. Therefore, this paper seeks to evaluate several processes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…The manipulation of process variables allows distinct products and colours compatible with market demands. However, it should be noted that the synthesis of pigments is sensible to the kind of chemicals chosen, concentrations applied, and the procedure in general [20].…”
Section: Resultsmentioning
confidence: 99%
“…The manipulation of process variables allows distinct products and colours compatible with market demands. However, it should be noted that the synthesis of pigments is sensible to the kind of chemicals chosen, concentrations applied, and the procedure in general [20].…”
Section: Resultsmentioning
confidence: 99%
“…Selective precipitation was optimized to obtain yellow pigment from AMD while simultaneously treating the water (Silva et al, 2019). The quality of the pigment strongly depended on the presence of contaminants.…”
Section: Recovery Of Resources From Mine Drainagementioning
confidence: 99%
“…Wei et al demonstrated that high recovery of both metals was possible in lime neutralization systems, albeit at a purity in the low 90% range [33]. The production of high purity iron products from AMD was demonstrated by reprocessing the low purity sludge using nitric acid and potassium hydroxide [34] and alternatively through the usage of high cost soda ash neutralization agent [35]. Both options however require expensive reagents to yield low value products.…”
Section: Introductionmentioning
confidence: 99%